225k views
5 votes
Identify the incorrect step in solving the expression

Identify the incorrect step in solving the expression-example-1
User Kazimad
by
6.1k points

2 Answers

5 votes

When you multiply an exponent directly into another exponent, you multiply the exponents.

For example:


(x^(2) )^6=x^(2(6))=x^(12)


(x^(4))^1=x^(4(1))=x^4




(5^(3))^2=5^(3(2))=5^6

So #2 is incorrect

User Hemant Parihar
by
5.9k points
5 votes

Answer: step 2, instead of adding the exponets together they should have done 5^3 first and then done the result of that (125) ^2

User TwinPrimesAreEz
by
6.9k points